Pengembangan Konten Pembelajaran Berbasis Canva pada Pokok Bahasan Asam-Basa (Universitas Negeri Semarang, 2023)
The use of technology in education has been widely used in the development of media and learning content. One application that can support the learning process is Canva. The purpose of this research is to describe the use of Canva media in creating innovative and creative digital-based learning content on acid-base topics using applications. The research method uses a descriptive qualitative approach and literature study as a result of utilizing existing features in Canva-based applications with the IDI (Instructional Development Institute) model. The result of this research is the creation of learning content with the subject of acid and base which is interactive and easy to understand by students. The conclusion is that teachers can take advantage of the features available in the Canva application to improve learning content so that learning activities are more interactive.